2021
DOI: 10.3390/land10121316
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of the Critically Endangered Araucaria angustifolia Tree Using Worldview-2 Images, Google Earth Engine and UAV-LiDAR

Abstract: The Brazilian Atlantic Forest is a global biodiversity hotspot and has been extensively mapped using satellite remote sensing. However, past mapping focused on overall forest cover without consideration of keystone plant resources such as Araucaria angustifolia. A. angustifolia is a critically endangered coniferous tree that is essential for supporting overall biodiversity in the Atlantic Forest. A. angustifolia’s distribution has declined dramatically because of overexploitation and land-use changes. Accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition to the presently utilized multispectral sensors, previous research has indicated that hyperspectral sensors [55] and LiDAR [56] could provide supplementary spatial information of predominately structural environmental conditions and could be successfully integrated with machine learning classification methods. UASs have also ensured high prediction accuracy in related studies for nature conservation, such as flora species population count and coverage area prediction [57,58]. Although machine learning classification methods, such as those evaluated in this study, are generally resistant to overfitting which might occur in the process, overfitting still might occur due to exaggerated pruning [59].…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the presently utilized multispectral sensors, previous research has indicated that hyperspectral sensors [55] and LiDAR [56] could provide supplementary spatial information of predominately structural environmental conditions and could be successfully integrated with machine learning classification methods. UASs have also ensured high prediction accuracy in related studies for nature conservation, such as flora species population count and coverage area prediction [57,58]. Although machine learning classification methods, such as those evaluated in this study, are generally resistant to overfitting which might occur in the process, overfitting still might occur due to exaggerated pruning [59].…”
Section: Discussionmentioning
confidence: 94%
“…Despite the free accessibility of high-resolution satellite images such as those from Sentinel-2 and Landsat 8, a number of ecological studies have utilized ultra-resolution and very high-resolution satellite images. Review of these studies indicates that ultraresolution and very high-resolution satellite images have been adapted mainly for the detection and mapping of small patches of vegetation such as endangered plants and invasive species [101][102][103][104] or for the differentiation and mapping of mixed vegetation in a heterogeneous environment [105][106][107]. The vegetation mixedness is a matter of the spatial resolution of the imagery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the accurate diagnosis and continuous monitoring of A. angustifolia in forest remnants are crucial for environmental preservation. With technological advances, Unmanned Aerial Vehicles (UAVs), or drones, have increasingly become versatile and accessible tools for research in this eld, enabling the mapping and monitoring of trees and forests (SAAD et al, 2021;ECKE et al, 2022;CUNHA NETO et al, 2023). Additionally, computer vision techniques used to analyze images from remote sensors, particularly those based on deep learning, more speci cally Convolutional Neural Networks (CNNs), have shown their potential in recognizing tree species in forest regions (KNAUER et al, 2019;SANTOS et al, 2019).…”
Section: Introductionmentioning
confidence: 99%